Severe digestive pathology associated with chronic Chaga's disease in Ecuador: report of two cases - Guevara,Angel G. (1997)
DNA extracted from peripheral blood of two Ecuadorian patients showing severe digestive pathology was amplified by the polymerase chain reaction using a Trypanosoma cruzi specific oligonucleotide primers derived from the primary sequence of a cDNA encoding for a 24 kDa excretory/secretory protein. The positive PCR results together with the clinical findings confirmed that both patients had a digestive pathology due to Chagas' disease. This pathology could be more frequent than previously described in the chagasic endemic regions of Andean countries.